Behçet’s Disease: An Overview of Etiopathogenesis - Leccese, Pietro; Alpsoy, Erkan (Frontiers in Immunology, 2019)
Behçet’s disease (BD) is a chronic, relapsing inflammatory multisystem disease of unknown etiology hallmarked predominantly by mucocutaneous lesions and ocular involvement. BD shares some common features with autoimmune and autoinflammatory diseases and spondyloarthropathies (MHC-I-opathies). It is related to more than one pathogenic pathway triggered by environmental factors such as infectious agents in genetically predisposed subjects. The interplay between a complex genetic background and both innate and adaptive immune system is linked to the BD presentation. Genetic factors have been investigated extensively, and several recent genome-wide association studies have confirmed HLA-B*51 to be the strongest genetic susceptibility factor and have identified new susceptibility genes both on the remaining part of HLA Class I region and on non-HLA genes for BD. Genetic variations in the genes encoding the cytokines may affect their function and be associated with disease predisposition. Infectious agents such as Streptococcus sanguinis or the differences in salivary or gut microbiome composition can be considered to trigger the innate-derived inflammation which is, subsequently, sustained by adaptive immune responses. Altered trimming of microbial and/or endogenous peptides by endoplasmic reticulum aminopeptidase 1 (ERAP1), presented by HLA-B*51, may play a key role in BD pathogenesis causing T cell homeostasis perturbation, especially Th1 and Th17 expansion and decreased regulation by Tregs. Neutrophil activity is increased in BD, and the affected organs show a significant neutrophil infiltration. HLA-B*51 association and increased IL-17 response are thought to be significantly involved in neutrophil activation. In this paper, we provide an overview of the most recent advances on BD ethiopathogenesis.